Characterization of abundance and diversity of lactic acid bacteria from Apis dorsata hives and flowers in East Nusa Tenggara, Indonesia - AMOR TRESNA KARYAWATI; LILIS NURAIDA; YULIN LESTARI; ANJA MERYANDINI (Biodiversitas Journal of Biological Diversity, 2018)
Karyawati AT, Nuraida L, Lestari Y, Meryandini A. 2018. Characterization of abundance and diversity of lactic acid bacteria from Apis dorsata hives and flowers in East Nusa Tenggara, Indonesia. Biodiversitas 19: 899-905. Previous research on lactic acid bacteria associated with honey bees has been conducted in temperate arid regions and wet tropical regions. We isolated lactic acid bacteria from giant honey bee (Apis dorsata) hives and flowers in East Nusa Tenggara, Indonesia, an area with a tropical savanna climate. Diversity of lactic acid bacteria was studied using Denaturing Gradient Gel Electrophoresis method. The purpose of this study was to obtain information about the diversity of lactic acid bacteria contained in Apis dorsata hives and flowers from tropical savanna climate. We identified seven Operational Taxonomy Units (OTU) within the hives and flowers. Two OTUs were closely related to LactoBacillus kunkeei strain YH-15 (T), while three others were closely related to Lactococcus lactis subsp. tructae strain L105 (T). This information is important to explore the potential utilization of lactic acid bacteria in maintaining human health.